PENGARUH OPINI AUDIT, AUDIT TENURE, KOMISARIS INDEPENDEN, DAN KEPEMILIKAN MANAJERIAL PADA KETEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN - Kristiantini, Made Dania; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
In order to provide benefits to its users, the financial statements must fulfill the qualitative characteristics. One of the qualitative characteristics is timeliness. This study has purpose to prove the effect of audit opinion, audit tenure, independent commissioners, and managerial ownership on the timeliness of financial reports publication of banking companies listed on the Indonesia Stock Exchange. This study use purposive sampling as its sampling technique. Data analysis technique used is logistic regression with significance 5%. The test results indicate that the audit opinion, audit tenure, independent commissioners, and managerial ownership positively affects the timeliness of financial statement publication banking companies listed in Indonesia Stock Exchange period 2013-2015.
Keywords: timeliness, audit opinion, audit tenure, independent commisioners, managerial ownership